The social construction of police heroes - Terpstra, Jan (International journal of police science & management, 2020)
This article deals with the social construction of police heroes, an important, but often neglected aspect in police research. The dramaturgical approach as developed by Goffman is used to understand how police heroes come into being and how they can fall into disgrace. The social construction of the police hero is studied first by looking at the person of Buford Pusser, a Tennessee sheriff in the 1960s and 1970s who has often been seen as the most famous American (police) hero. From the dramaturgical perspective three different patterns can be distinguished that can contribute to the instability of police heroism and that can result in the fall of the hero into disgrace. Finally, it is suggested that social meaning and practices of police heroism are highly dependent on their cultural context.